The left hand of darkness - Le Guin, Ursula K. 1929- (New York Ace Books, 2000)
A human emissary sent to the world of Winter to bring it into a galactic civilization must find a way to bridge the gulf between his outlook and that of the natives, who can change gender at will.
A Parade in Erhenrang -- The Place Inside the Blizzard -- The Mad King -- The Nineteenth Day -- The Domestication of Hunch -- One Way into Orgoreyn -- The Question of Sex -- Another Way into Orgoreyn -- Eestraven the Traitor -- Conversations in Mishnory -- Soliloquies in Mishnory -- On Time and Darkness -- Down on the Farm -- The Escape -- To the Ice -- Between Drumner and Dremegole -- An Orgota Creation Myth -- On the Ice -- Homecoming -- A Fool's Errand -- The Gethenian Calendar and Clock.
Keywords: Science fiction